Assessing the carbon assimilation and production of benthic archaeal lipid biomarkers using lipid-RIP. (15th November 2019) - Evans, Thomas W.; Coffinet, Sarah; Könneke, Martin; Lipp, Julius S.; Becker, Kevin W.; Elvert, Marcus; Heuer, Verena; Hinrichs, Kai-Uwe
Abstract: Distributional patterns of intact polar lipids (IPLs) suggest that archaea are abundant in marine subsurface sediments. However, the production of archaeal lipids remains largely unresolved. We performed a lipid radioisotope probing (lipid-RIP) experiment using 14 C-bicarbonate and 2- 14 C-acetate with surface and methanogenic marine sediments from the Rhone delta (Mediterranean Sea) to investigate mechanisms of carbon assimilation and to assess biomass production of benthic archaea. The direct determination of carbon assimilation rates into diagnostic IPLs in the experiments with 14 C-bicarbonate were up to 9 times higher than in the incubations with 2- 14 C-acetate, implying that autotrophy is an important carbon pathway for the benthic archaea in the Rhone delta sediments. Production rates of polyglycosidic archaeols (AR) were one to two orders of magnitude higher than those of mono- and polyglycosidic glycerol dialkyl glycerol tetraethers (GDGTs), suggesting that the former IPLs are good biomarkers for active benthic archaea in marine sediments. In contrast, the low production rates of the monoglycosidic AR and GDGTs, indicate that a large fraction of these IPLs may represent fossil sedimentary remains from the water column. Unexpectedly, the lipid production rates of AR and GDGT core lipids (CLs) were similar to those of polyglycosidic IPLs. Considering the relatively short period of incubation (21 days), this suggests that CLs may be actively synthesized by benthic archaea in marine sediments and are not exclusively formed from the degradation of IPL precursors.